Good Fences Make Good Neighbors: Adjacent Honey Bee Colonies Locally Partition Their Foraging Across Landscapes - Bradley D. Ohlinger; Margaret J. Couvillon; Laurence W. Carstensen; Roger Schürch (Ecology and Evolution)
ABSTRACT Optimal foraging theory (OFT) predicts that animals employ foraging strategies that maximize a particular currency, such as net energetic efficiency, to meet their nutritional demands. Two nonexclusive patterns that arise from OFT are convergence on high‐quality resources and resource partitioning. Honey bees make collective decisions by integrating their individual foraging with social recruitment behaviors: returning foragers communicate the approximate vector to high‐quality resources using waggle dances. Because we can eavesdrop on their communications, waggle dance decoding is a valuable tool for exploring OFT predictions as it allows us to map how honey bees use landscapes. In this study, we analyzed 8049 dances from colocalized colonies across three landscapes to investigate whether neighboring colonies forage by not partitioning patches (i.e., converging their food collection on the same patches), by partitioning at the landscape level, or by partitioning at the local level. To differentiate between these three possible scenarios, we examined three metrics: (1) interdance distances between and within colonies; (2) k‐nearest neighbors; and (3) k‐means clustering. We observed no difference in the distances between dances performed by bees from the same colony compared to those from different colonies. Also, we found at each of the three field sites that dances from the same colony were not more likely to appear as close neighbors to each other. Finally, k‐means cluster analysis demonstrates that dance locations advertised by the same colony aggregated nonrandomly in the three sites, where dances from the same colony comprised a significant majority of dances within k‐means clusters and 62% of clusters consisted entirely of dances from a single colony. Together, these results support a foraging scenario where honey bees partition their foraging, but at the local level. This strategy may help limit intercolony foraging competition.